Rapid changes in transcription during a feast-famine event - Paul Dijkstra; Bruce A. Hungate; Jennifer Pett-Ridge; Steven J. Blazewicz; Javier A. Ceja-Navarro; Ember M. Morrissey; Peter F. Chuckran; Egbert Schwartz (Soil Biology and Biochemistry, 2026)

Shrub and sedge rhizosphere communities display distinct affinities toward exudates and soil organic matter degradation: a quantitative stable isotope probing analysis - Sean R. Schaefer; Steven J. Blazewicz; Hannah Holland-Moritz; Caitlin Hicks Pries; G. Mike Allen; Jennifer Pett-Ridge; Fernando Montaño-López; A. Stuart Grandy; William Wieder; Jessica G. Ernakovich (Soil Biology and Biochemistry, 2026)

Drought Reduces Formation, but Enhances Persistence, of Mineral‐Associated Organic Matter in a Grassland Soil - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Nicole DiDonato; Katerina Estera‐Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; William Kew; Ljiljana Paša‐Tolić; Eric Slessarev; Jennifer Pett‐Ridge (Global Change Biology, 2026)
Drought effects are pervasive in terrestrial ecosystems, yet there is limited understanding of how drought impacts the transformation of plant carbon (C) inputs to mineral‐associated organic matter (MAOM)—the largest and slowest‐cycling pool of soil organic carbon (SOC). In a 12‐week 13 C‐CO 2 greenhouse labeling experiment, we tracked the formation of MAOM derived from the two dominant sources of plant C input to the mineral soil—living root inputs ( 13 C‐rhizodeposits) and decaying root inputs ( 13 C‐root detritus)—under normal moisture and droughted conditions in a semiarid grassland soil. At the end of the 12‐week period, we also measured the persistence of 13 C‐MAOM formed from rhizodeposits versus root detritus via a subsequent persistence assay. Drought reduced the formation of MAOM derived from living roots by decreasing rhizodeposits, reducing microbial growth rates, and altering the composition of organic matter, lipids, and metabolites. Drought initially delayed the formation of MAOM derived from root detritus by slowing the early stages of root litter decomposition (week 4–8), but did not decrease total MAOM formation by the end of the 12‐week period. Notably, drought enhanced the persistence of MAOM derived from root detritus, but did not influence the persistence of MAOM derived from rhizodeposits. Our results provide some of the first direct evidence that drought can reduce the formation of MAOM in a grassland soil, but may enhance its persistence, based on the source of plant input from which MAOM is derived.

Composition, Growth, Succession, and Function in the Cladophora Microbiome: Insights From Quantitative Stable Isotope Probing and NanoSIMS Imaging - Raina M. Fitzpatrick; Bruce A. Hungate; Mary Power; Megan Foley; Ty Samo; Egbert Schwartz; Micheala Hayer; Peter K. Weber; Jennifer Pett‐Ridge; Jane C. Marks (Environmental Microbiology, 2025)
The branching green macroalga Cladophora glomerata and its epiphytic microbiome dominate summer biomass in the Eel River, a Northern California river under Mediterranean (summer drought, winter rain) seasonality. Green Cladophora streamers proliferate in early summer, then change to yellow and then red‐brown as epiphyte loads increase. We characterised successional changes in epiphytic bacteria on Cladophora , examining both community composition and growth rates, using quantitative Stable Isotope Probing (qSIP) and 16S rRNA gene amplicon sequencing. The number of bacterial taxa increased with succession while growth rates peaked in the middle stage. NanoSIMS imaging confirmed high sulphur (S) concentrations in Cladophora cell walls relative to surrounding biomass, coinciding with a bloom of sulphur bacteria (bacteria that reduce or oxidise sulphur/sulphates). In general, relative abundances and growth rates were independent, indicating that either metric alone is insufficient for understanding how taxonomy and functional groups affect ecosystem processes. For instance, the relative abundance of nitrogen fixers peaked in the late summer when their relative growth rates were slowest. Such patterns may be driven by space competition limiting growth. Together, changes in abundance and relative growth rates suggest different limiting factors for different functional groups in the Cladophora microbiome at multiple successional stages.

Phosphate amendment drives bloom of RNA viruses after soil wet-up - Ella T. Sieradzki; G. Michael Allen; Jeffrey A. Kimbrel; Graeme W. Nicol; Christina Hazard; Erin Nuccio; Steven J. Blazewicz; Jennifer Pett-Ridge; Gareth Trubl (Soil Biology and Biochemistry, 2025)

Beneath the surface: Unsolved questions in soil virus ecology - Christina Hazard; Karthik Anantharaman; Luke S. Hillary; Uri Neri; Simon Roux; Gareth Trubl; Kurt Williamson; Jennifer Pett-Ridge; Graeme W. Nicol; Joanne B. Emerson (Soil Biology and Biochemistry, 2025)

Getting to the root of the problem: Soil carbon and microbial responses to root inputs within a buried paleosol along an eroding hillslope in southwestern Nebraska, USA - Abbygail R. McMurtry; Chase S. Kasmerchak; Elliot A. Vaughan; Manisha Dolui; Laura M. Phillips; Carsten W. Mueller; Jennifer Pett-Ridge; Asmeret Asefaw Berhe; Joseph A. Mason; Erika Marín-Spiotta; Marie-Anne de Graaff (Soil Biology and Biochemistry, 2024)

Exploring viral particle, soil, and extraction buffer physicochemical characteristics and their impacts on extractable viral communities - Jane D. Fudyma; Anneliek M. ter Horst; Christian Santos-Medellín; Jess W. Sorensen; Grant G. Gogul; Luke S. Hillary; Sara E. Geonczy; Jennifer Pett-Ridge; Joanne B. Emerson (Soil Biology and Biochemistry, 2024)

The path from root input to mineral-associated soil carbon is dictated by habitat-specific microbial traits and soil moisture - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Amrita Bhattacharyya; Nicole DiDonato; Katerina Estera-Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; Jeffrey Kimbrel; Jose Liquet; Marissa Lafler; et al. (Soil Biology and Biochemistry, 2024)

Edaphic controls on genome size and GC content of bacteria in soil microbial communities - Peter F. Chuckran; Cody Flagg; Jeffrey Propster; William A. Rutherford; Ella T. Sieradzki; Steven J. Blazewicz; Bruce Hungate; Jennifer Pett-Ridge; Egbert Schwartz; Paul Dijkstra (Soil Biology and Biochemistry, 2023)

Nutrients strengthen density dependence of per-capita growth and mortality rates in the soil bacterial community - Bram W. Stone; Steven J. Blazewicz; Benjamin J. Koch; Paul Dijkstra; Michaela Hayer; Kirsten S. Hofmockel; Xiao Jun Allen Liu; Rebecca L. Mau; Jennifer Pett-Ridge; Egbert Schwartz; Bruce A. Hungate (Oecologia, 2023)

Initial soil organic carbon stocks govern changes in soil carbon: Reality or artifact? - Eric W. Slessarev; Allegra Mayer; Courtland Kelly; Katerina Georgiou; Jennifer Pett‐Ridge; Erin E. Nuccio (Global Change Biology, 2023)
Changes in soil organic carbon (SOC) storage have the potential to affect global climate; hence identifying environments with a high capacity to gain or lose SOC is of broad interest. Many cross‐site studies have found that SOC‐poor soils tend to gain or retain carbon more readily than SOC‐rich soils. While this pattern may partly reflect reality, here we argue that it can also be created by a pair of statistical artifacts. First, soils that appear SOC‐poor purely due to random variation will tend to yield more moderate SOC estimates upon resampling and hence will appear to accrue or retain more SOC than SOC‐rich soils. This phenomenon is an example of regression to the mean. Second, normalized metrics of SOC change—such as relative rates and response ratios—will by definition show larger changes in SOC at lower initial SOC levels, even when the absolute change in SOC does not depend on initial SOC. These two artifacts create an exaggerated impression that initial SOC stocks are a major control on SOC dynamics. To address this problem, we recommend applying statistical corrections to eliminate the effect of regression to the mean, and avoiding normalized metrics when testing relationships between SOC change and initial SOC. Careful consideration of these issues in future cross‐site studies will support clearer scientific inference that can better inform environmental management.

Constraining the composition and quantity of organic matter used by abundant marine Thaumarchaeota - Alma E. Parada; Xavier Mayali; Peter K. Weber; Jessica Wollard; Alyson E. Santoro; Jed A. Fuhrman; Jennifer Pett‐Ridge; Anne E. Dekas (Environmental Microbiology, 2023)
Marine Group I (MGI) Thaumarchaeota were originally described as chemoautotrophic nitrifiers, but molecular and isotopic evidence suggests heterotrophic and/or mixotrophic capabilities. Here, we investigated the quantity and composition of organic matter assimilated by individual, uncultured MGI cells from the Pacific Ocean to constrain their potential for mixotrophy and heterotrophy. We observed that most MGI cells did not assimilate carbon from any organic substrate provided (glucose, pyruvate, oxaloacetate, protein, urea, and amino acids). The minority of MGI cells that did assimilate it did so exclusively from nitrogenous substrates (urea, 15% of MGI and amino acids, 36% of MGI), and only as an auxiliary carbon source (

Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands - Megan M. Foley; Steven J. Blazewicz; Karis J. McFarlane; Alex Greenlon; Michaela Hayer; Jeffrey A. Kimbrel; Benjamin J. Koch; Victoria L. Monsaint-Queeney; Keith Morrison; Ember Morrissey; Bruce A. Hungate; Jennifer Pett-Ridge (Soil Biology and Biochemistry, 2023)

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Hyphae move matter and microbes to mineral microsites: Integrating the hyphosphere into conceptual models of soil organic matter stabilization - Craig R. See; Adrienne B. Keller; Sarah E. Hobbie; Peter G. Kennedy; Peter K. Weber; Jennifer Pett‐Ridge (Global Change Biology, 2022)
Associations between soil minerals and microbially derived organic matter (often referred to as mineral‐associated organic matter or MAOM) form a large pool of slowly cycling carbon (C). The rhizosphere, soil immediately adjacent to roots, is thought to control the spatial extent of MAOM formation because it is the dominant entry point of new C inputs to soil. However, emphasis on the rhizosphere implicitly assumes that microbial redistribution of C into bulk (non‐rhizosphere) soils is minimal. We question this assumption, arguing that because of extensive fungal exploration and rapid hyphal turnover, fungal redistribution of soil C from the rhizosphere to bulk soil minerals is common, and encourages MAOM formation. First, we summarize published estimates of fungal hyphal length density and turnover rates and demonstrate that fungal C inputs are high throughout the rhizosphere–bulk soil continuum. Second, because colonization of hyphal surfaces is a common dispersal mechanism for soil bacteria, we argue that hyphal exploration allows for the non‐random colonization of mineral surfaces by hyphae‐associated taxa. Third, these bacterial communities and their fungal hosts determine the chemical form of organic matter deposited on colonized mineral surfaces. Collectively, our analysis demonstrates that omission of the hyphosphere from conceptual models of soil C flow overlooks key mechanisms for MAOM formation in bulk soils. Moving forward, there is a clear need for spatially explicit, quantitative research characterizing the environmental drivers of hyphal exploration and hyphosphere community composition across systems, as these are important controls over the rate and organic chemistry of C deposited on minerals.

Decreased growth of wild soil microbes after 15 years of transplant‐induced warming in a montane meadow - Alicia M. Purcell; Michaela Hayer; Benjamin J. Koch; Rebecca L. Mau; Steven J. Blazewicz; Paul Dijkstra; Michelle C. Mack; Jane C. Marks; Ember M. Morrissey; Jennifer Pett‐Ridge; Rachel L. Rubin; Egbert Schwartz; et al. (Global Change Biology, 2022)
The carbon stored in soil exceeds that of plant biomass and atmospheric carbon and its stability can impact global climate. Growth of decomposer microorganisms mediates both the accrual and loss of soil carbon. Growth is sensitive to temperature and given the vast biological diversity of soil microorganisms, the response of decomposer growth rates to warming may be strongly idiosyncratic, varying among taxa, making ecosystem predictions difficult. Here, we show that 15 years of warming by transplanting plant–soil mesocosms down in elevation, strongly reduced the growth rates of soil microorganisms, measured in the field using undisturbed soil. The magnitude of the response to warming varied among microbial taxa. However, the direction of the response—reduced growth—was universal and warming explained twofold more variation than did the sum of taxonomic identity and its interaction with warming. For this ecosystem, most of the growth responses to warming could be explained without taxon‐specific information, suggesting that in some cases microbial responses measured in aggregate may be adequate for climate modeling. Long‐term experimental warming also reduced soil carbon content, likely a consequence of a warming‐induced increase in decomposition, as warming‐induced changes in plant productivity were negligible. The loss of soil carbon and decreased microbial biomass with warming may explain the reduced growth of the microbial community, more than the direct effects of temperature on growth. These findings show that direct and indirect effects of long‐term warming can reduce growth rates of soil microbes, which may have important feedbacks to global warming.

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

The role of soil redox conditions in microbial phosphorus cycling in humid tropical forests - Avner Gross; Yang Lin; Peter K. Weber; Jennifer Pett‐Ridge; Whendee L. Silver (Ecology, 2020)
Humid tropical forests are among the most productive ecosystems globally, yet they often occur on soils with high phosphorus (P) sorption capacity, lowering P availability to biota. Short‐term anoxic events are thought to release sorbed P and enhance its acquisition by soil microbes. However, the actual effects of anoxic conditions on microbial P acquisition in humid tropical forest soils are surprisingly poorly studied. We used laboratory incubations of bulk soils, NanoSIMS analysis of single microbial cells, and landscape‐scale measurements in the Luquillo Experimental Forest (LEF), Puerto Rico to test the hypothesis that anoxic conditions increase microbial P acquisition in humid tropical forests. In laboratory and field experiments, we found that microbial P uptake generally decreased under anoxic conditions, leading to high microbial carbon (C) to P ratios in anoxic soils. The decreased P acquisition under anoxic conditions was correlated with lower microbial C use efficiency (CUE), an index of microbial energy transfer in ecosystems. Phosphorus amendments to anoxic soils led to increased microbial P uptake and higher CUE suggesting that microbes were less able to access and utilize P under natural low redox conditions. Under oxic conditions, microbial C:P ratios and CUE did not respond to changes in substrate stoichiometry. These results challenge the existing paradigm by showing that anoxic conditions can decrease microbial P uptake and ultimately constrain microbial CUE. Our findings indicate that soil redox conditions tightly couple soil P and C cycles and advance our understanding of controls on P cycling in humid tropical forest ecosystems.

Attachment between heterotrophic bacteria and microalgae influences symbiotic microscale interactions - Ty J. Samo; Jeffrey A. Kimbrel; Daniel J. Nilson; Jennifer Pett‐Ridge; Peter K. Weber; Xavier Mayali (Environmental Microbiology, 2018)
Summary The surface and surroundings of microalgal cells (phycosphere) are critical interaction zones but have been difficult to functionally interrogate due to methodological limitations. We examined effects of phycosphere‐associated bacteria for two biofuel‐relevant microalgal species ( Phaeodactylum tricornutum and Nannochloropsis salina ) using stable isotope tracing and high spatial resolution mass spectrometry imaging (NanoSIMS) to quantify elemental exchanges at the single‐cell level. Each algal species responded differently to bacterial attachment. In P. tricornutum , a high percentage of cells had attached bacteria (92%–98%, up to eight bacteria per alga) and fixed 64% more carbon with attached bacteria compared to axenic cells. In contrast, N. salina cells were less commonly associated with bacteria (42%–63%), harboured fewer bacteria per alga, and fixed 10% more carbon without attached bacteria compared to axenic cells. An uncultivated bacterium related to Haliscomenobacter sp. was identified as an effective mutualist; it increased carbon fixation when attached to P. tricornutum and incorporated 71% more algal‐fixed carbon relative to other bacteria. Our results illustrate how phylogenetic identity and physical location of bacteria and algae facilitate diverse metabolic responses. Phycosphere‐mediated, mutualistic chemical exchanges between autotrophs and heterotrophs may be a fruitful means to increase microalgal productivity for applied engineering efforts.

Microbial community assembly differs across minerals in a rhizosphere microcosm - Thea Whitman; Rachel Neurath; Adele Perera; Ilexis Chu‐Jacoby; Daliang Ning; Jizhong Zhou; Peter Nico; Jennifer Pett‐Ridge; Mary Firestone (Environmental Microbiology, 2018)
Summary Mineral‐associated microbes drive many critical soil processes, including mineral weathering, soil aggregation and cycling of mineral‐sorbed organic matter. To investigate the interactions between soil minerals and microbes in the rhizosphere, we incubated three types of minerals (ferrihydrite, kaolinite and quartz) and a native soil mineral fraction near roots of a common Californian annual grass, Avena barbata , growing in its resident soil. We followed microbial colonization of these minerals for up to 2.5 months – the plant's lifespan. Bacteria and fungi that colonized mineral surfaces during this experiment differed across mineral types and differed from those in the background soil, implying that microbial colonization was the result of processes in addition to passive movement with water to mineral surfaces. Null model analysis revealed that dispersal limitation was a dominant factor structuring mineral‐associated microbial communities for all mineral types. Once bacteria arrived at a mineral surface, capacity for rapid growth appeared important, as ribosomal copy number was significantly correlated with relative enrichment on minerals. Glomeromycota (a phylum associated with arbuscular mycorrhizal fungi) appeared to preferentially associate with ferrihydrite surfaces. The mechanisms enabling the colonization of soil minerals may be foundational in shaping the overall soil microbiome composition and development of persistent organic matter in soils.

Climate and edaphic controllers influence rhizosphere community assembly for a wild annual grass - Erin E. Nuccio; James Anderson‐Furgeson; Katerina Y. Estera; Jennifer Pett‐Ridge; Perry de Valpine; Eoin L. Brodie; Mary K. Firestone (Ecology, 2016)
The interface between roots and soil, known as the rhizosphere, is a dynamic habitat in the soil ecosystem. Unraveling the factors that control rhizosphere community assembly is a key starting point for understanding the diversity of plant‐microbial interactions that occur in soil. The goals of this study were to determine how environmental factors shape rhizosphere microbial communities, such as local soil characteristics and the regional climate, and to determine the relative influence of the rhizosphere on microbial community assembly compared to the pressures imposed by the local and regional environment. We identified the bacteria present in the soil immediately adjacent to the roots of wild oat ( Avena spp .) in three California grasslands using deep Illumina 16S sequencing. Rhizosphere communities were more similar to each other than to the surrounding soil communities from which they were derived, despite the fact that the grasslands studied were separated by hundreds of kilometers. The rhizosphere was the dominant factor structuring bacterial community composition (38% variance explained), and was comparable in magnitude to the combined local and regional effects (22% and 21%, respectively). Rhizosphere communities were most influenced by factors related to the regional climate (soil moisture and temperature), while background soil communities were more influenced by soil characteristics ( pH , CEC , exchangeable cations, clay content). The Avena core microbiome was strongly phylogenetically clustered according to the metrics NRI and NTI , which indicates that selective processes likely shaped these communities. Furthermore, 17% of these taxa were not detectable in the background soil, even with a robust sequencing depth of approximately 70,000 sequences per sample. These results support the hypothesis that roots select less abundant or possibly rare populations in the soil microbial community, which appear to be lineages of bacteria that have made a physiological tradeoff for rhizosphere competence at the expense of their competitiveness in non‐rhizosphere soil.

An arbuscular mycorrhizal fungus significantly modifies the soil bacterial community and nitrogen cycling during litter decomposition - Erin E. Nuccio; Angela Hodge; Jennifer Pett‐Ridge; Donald J. Herman; Peter K. Weber; Mary K. Firestone (Environmental Microbiology, 2013)
Summary Arbuscular mycorrhizal fungi ( AMF ) perform an important ecosystem service by improving plant nutrient capture from soil, yet little is known about how AMF influence soil microbial communities during nutrient uptake. We tested whether an AMF modifies the soil microbial community and nitrogen cycling during litter decomposition. A two‐chamber microcosm system was employed to create a root‐free soil environment to control AMF access to 13 C ‐ and 15 N ‐labelled root litter. Using a 16 S rRNA gene microarray, we documented that approximately 10% of the bacterial community responded to the AMF , G lomus hoi . Taxa from the F irmicutes responded positively to AMF , while taxa from the Actinobacteria and Comamonadaceae responded negatively to AMF . Phylogenetic analyses indicate that AMF may influence bacterial community assembly processes. Using nanometre‐scale secondary ion mass spectrometry ( NanoSIMS ) we visualized the location of AMF ‐transported 13 C and 15 N in plant roots. Bulk isotope ratio mass spectrometry revealed that the AMF exported 4.9% of the litter 15 N to the host plant ( P lantago lanceolata L .), and litter‐derived 15 N was preferentially exported relative to litter‐derived 13 C . Our results suggest that the AMF primarily took up N in the inorganic form, and N export is one mechanism by which AMF could modify the soil microbial community and decomposition processes.

PLANT AND MICROBIAL CONTROLS ON NITROGEN RETENTION AND LOSS IN A HUMID TROPICAL FOREST - Pamela H. Templer; Whendee L. Silver; Jennifer Pett-Ridge; Kristen M. DeAngelis; Mary K. Firestone (Ecology, 2008)
Humid tropical forests are generally characterized by the lack of nitrogen (N) limitation to net primary productivity, yet paradoxically have high potential for N loss. We conducted an intensive field experiment with 15 NH 4 and 15 NO 3 additions to highly weathered tropical forest soils in Puerto Rico to determine the relative importance of N retention and loss mechanisms. Over one‐half of all the NH 4 + produced was rapidly converted to NO 3 − via the process of gross nitrification. During the first 24 hours, plant roots took up 28% of the inorganic N produced, dominantly as NH 4 + , and were a greater sink for N than soil microbial biomass. Soil microbes were not a significant sink for added 15 NH 4 + or 15 NO 3 − during the first 24 hours, and only for 15 NH 4 + after 7 days. Patterns of microbial community composition, as determined by terminal restriction fragment length polymorphism analysis (TRFLP), were weakly but significantly correlated with nitrification and denitrification to N 2 O. Rates of dissimilatory NO 3 − reduction to NH 4 + (DNRA) were high in this forest, accounting for up to 25% of gross NH 4 + production and 35% of gross nitrification. DNRA was a major sink for NO 3 − , which may have contributed to the lower rates of N 2 O and leaching losses. Despite considerable N conservation via DNRA and plant NH 4 + uptake, the fate of ∼ 45% of the NO 3 − produced and 4% of the NH 4 + produced were not measured in our fluxes, suggesting that other important pathways for N retention and loss (e.g., denitrification to N 2 ) are important in this system. The high proportion of mineralized N that was rapidly nitrified and the fates of that NO 3 − highlight the key role of gross nitrification as a proximate control on N retention and loss in humid tropical forest soils. Furthermore, our results demonstrate the importance of the coupling between DNRA and plant uptake of NH 4 + as a potential N‐conserving mechanism within tropical forests.